MERETAS MOTIVASI BELAJAR PESERTA DIDIK DI ERA PANDEMI MELALUI VIDEO VIRTUAL LABORATORY - Wahyuni Budi Hastuti (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2021)
Students' lack of enthusiasm in learning science-physics online during a pandemic requires the writer to look for small breakthroughs in the learning process of Dynamic Electricity material. PhET (Physical Education Technology) can be used as an alternative virtual media to guide students to learn science concepts hands-on and mind-on with enthusiasm. This article is a resume of a learning test using a virtual laboratory on dynamic electricity material for MTsN science subjects. The learning test aims to see the motivation of students towards learning and measure their learning outcomes. In this case study, observation, interview, and test techniques were used. The statements concluded that the use of PhET in online learning activities received a very positive response from students, as indicated by their response and enthusiasm. Good response and reasonable confidence impact the evaluation results, which show 86% of students achieve completeness with a KKM value = 75.